2021
DOI: 10.1111/bjd.20411
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiotic gut microbiota in patients with inflammatory rosacea: another clue towards the existence of a brain–gut–skin axis

Abstract: D levels. 4 Therefore, we hypothesize that patients with BCC have higher vitamin D levels, which may protect against severe COVID-19 outcomes. While serum 25-hydroxyvitamin D has been positively associated with melanoma and keratinocyte carcinoma, particularly BCC, 5,6 there may be other residual confounders in patients with COVID-19 with SCC and melanoma that were impossible to elucidate from the data, such as duration of immunosuppression, severity of chronic skin inflammation and genetic make-up, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…On the other hand, studies characterizing the gut microbiota of rosacea patients based on NGS are also scarce. In this regard, significant differences have been consistently identified at genera level between rosacea patients and rosacea-free individuals ( Nam et al, 2018 ; Chen et al, 2021 ; Moreno-Arrones et al, 2021 ). All these findings at skin and gut microbiota level reinforce the role of the skin-gut axis in the pathophysiology of rosacea.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, studies characterizing the gut microbiota of rosacea patients based on NGS are also scarce. In this regard, significant differences have been consistently identified at genera level between rosacea patients and rosacea-free individuals ( Nam et al, 2018 ; Chen et al, 2021 ; Moreno-Arrones et al, 2021 ). All these findings at skin and gut microbiota level reinforce the role of the skin-gut axis in the pathophysiology of rosacea.…”
Section: Discussionmentioning
confidence: 97%
“…The most recently published study is that of Moreno-Arrones et al evaluating the gut microbiota of 15 PPR patients (mean age 36 years, 80% females) and 15 controls (mean age 39 years, 33% females) ( Moreno-Arrones et al, 2021 ). The CHAO1 richness index was increased in PPR patients.…”
Section: Analysis Of the Gut Microbiota In Rosacea Patientsmentioning
confidence: 99%
“…Our study showed the protective effects of the genus Prevotella7 against melanoma and rosacea and the likely protective effects of the genus Prevotella9 against psoriasis. An analysis of the gut microbiota of 15 rosacea patients and 15 healthy individuals showed that Prevotella was more enriched in the intestines of healthy individuals than in patients ( Moreno-Arrones et al., 2021 ). Given that Prevotella has been found to be more scarce in the gut of Parkinson’s disease patients and that rosacea and Parkinson’s disease are epidemiologically linked, further exploration of the role of this bacterium in the brain–gut–skin axis is warranted ( Egeberg et al., 2016 ; Gerhardt and Mohajeri, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was potentially mediated by modulation of the gastrointestinal (GI) microbiota. Altered GI microbiota, a pivotal element of gut-skin axis, has been observed by emerging studies in rosacea and might be responsible for increased risks of GI comorbidities in rosacea ( 37 , 38 ). Multiple nutrients from MD, including polyphenols, polyunsaturated fatty acids (PUFAs) and fiber, contribute to modulations of the gut microbiota both in the aspects of diversity and inflammatory response ( 39 ).…”
Section: Discussionmentioning
confidence: 99%